(untitled) (ModaPalavra e-periódico, 2025)
This article examines the field of Haute Couture, institutionally established in Paris during the 1960-1970 period and initially analyzed by Pierre Bourdieu and Yvette Delsaut in 1975, in the work “Le couturier et sa griffe: contribution à une théorie de la magie” (The couturier and his signature: contribution to a theory of magic). Situated at the intersection of fashion and luxury, this study re-examine contemporary manifestations of the structure/agency dichotomy - a fundamental construct in Bourdieusian sociology. Through a methodological framework of rhetorical analysis applied to media representations, new possibilities of structuring brands are investigated, redrawing the classic diagram proposed by the autor and redimensioning contemporary positions in a field that exerts a significant symbolic impact on fashion and luxury markets. It also addresses emergent forms of agency between luxury brand and consumer, a theoretical gap in Bourdieu’s original framework. The results demonstrate how traditional structures of distinction remain in the midst of innovative brands’s strategies (such as Launchmetrics) and consumer agencies digitally transformed, with new dynamics of symbolic legitimacy.